TINJAUAN HUKUM ISLAM TERHADAP ‎PEMBATALAN PEMINANGAN MASYARAKAT ‎MUSLIM DI KEC. RAHUNING KABUPATEN ASAHAN - Dinata, Alfata (Jurnal Ushuluddin, 2022)
Marriage as stated in the Qur'an and the Law will be achieved well and perfectly if from the initial process. Therefore, the media of the proposal is very appropriate for ta'aruf or getting to know each other. Getting to know what is meant isn’t only knowing their personal identity but more than that is understanding and knowing the characteristics of the prospective husband and wife, the process of canceling the engagement according to custom, the factors causing and affecting the cancellation of the engagement, the review of Islamic Law on the process of canceling the engagement. The results of the problem community shouldn’t be excessive in the engagement process so that the chances of canceling the engagement will be even smaller. In canceling the engagement, it must be thought about first, even though the party who canceled gets compensation, at least we need to remember that a person's disappointment and hurt cannot be paid for with anything. Resolving disputes due to the cancellation of an engagement or in Islamic law called khitbah, the cancellation should be based on the right and clear reasons, although better than divorce after marriage, but this will cause trauma for someone whose engagement is cancelled.